Impact of Unemployment on Economic Growth in Nigeria: Bound Test and ARDL Approach - Olayemi, Henry Omotayo; Maku, Olukayode Emmanuel; Adelowokan, Oluwaseyi Adedayo (Acta Universitatis Danubius. Œconomica, 2023)
This study examined the impact of unemployment on economic growth in Nigeria. And based on the literature reviewed, the identified gaps were found in the scope, appropriate control variables and estimation techniques for the robustness of the findings. Data was sourced from the publications of World Bank-World Development Indicator, International Labour Organisation and Central Bank of Nigeria (CBN Statistical Bulletin) from 1980 – 2019 and various diagnostic tests such as Unit Roots and Bound Tests were carried out. Consequently, ARDL model was utilized to address the objective of this study. It was found out that unemployment had a positive and significant impact on economic growth both in the short run and in the long run. Furthermore, based on the findings, the paper recommended the introduction of programmes and policies that will promote enabling business environment to enable the teeming unemployed population to contribute to economic growth in Nigeria.